Priapism as an initial presentation in Chronic Myeloid Leukemia (CML): a case report - Ni Luh Putu Herawati; Tjokorda Gde Dharmayuda (DiscoverSys Inc., 2021)
Background: Priapism is a persistent, usually painful erection that lasts for more than four hours and occurs without sexual stimulation. Priapism is a rare clinical sign of Chronic Myeloid Leukemia (CML), with an incidence of 1-5 cases per 100,000 people per year. In men who suffer from CML, ischemic priapism occurs secondary to hyperleukocytosis and venous obstruction by thrombus and microthrombus. Case Presentation: In this case, a 24-year-old male, a Balinese ethnicity, present with prolonged erectile complaints accompanied by increased pain. From the examination performed, it was concluded that the patients had the ischemic type of priapism. From CBC, the patient was obtained hyperleukocytosis and continued with peripheral blood smear and bone marrow puncture. The patients concluded with CML, and initial intervention includes therapeutic aspiration, irrigation, hydroxyurea and other supportive therapies. It is a urological emergency requiring urgent treatment to prevent long-term complications, in particular erectile dysfunction.Conclusion: Priapism is an unusual clinical manifestation of CML, whereas priapism is a urological emergency requiring immediate therapy. Treatment delay can cause complications of erectile dysfunction in men.